Analisis Multi Peran Ibu Rumah Tangga di Desa Slogoretno Kecamatan Jatipurno Kabupaten Wonogiri - Ika Puji Lestari; Eny Lestari; Retno Setyowati (AGRITEXTS: Journal of Agricultural Extension, 2024)
Housewives who participate as workers will experience multiple roles in their lives. The involvement of women in the workforce has the consequence of limiting time in work and family life. Understanding the balance of roles is essential because it can give rise to positive and negative impacts from these multiple roles. This research aims to describe and analyze the roles of housewives and gender relations in the family. This research method is descriptive qualitative with a case study approach. The process for determining informants was carried out purposively with the criteria of coming from a complete farming family (husband and wife) and the wife taking part in instant herbal medicine processing so that 22 informants consisting of the Slogoretno Village Head (1 person), a housewife and her husband (10 pairs), chairman of the family welfare empowerment (PKK) of Slogoretno Village (1 person). Data collection techniques include in-depth interviews, observation, and documentation, employing Miles and Huberman’s interactive analysis and Harvard gender analysis methodologies. Data validity uses triangulation of sources and methods. The results obtained in this research are that the multi-role forms carried out by housewives, especially in farming families, are divided into 7 roles, namely the roles of mother, wife, worker, relative, and roles in domestic, community, and individual activities. The gender dynamics established often involve patterns of cooperation in role division and decision-making, affecting access, control, and benefits related to resources. In Slogoretno Village, the division of roles within farming families reveals that wives and husbands primarily handle reproductive tasks, while productive and social roles are typically shared.